(untitled) (Eurasian Scientific Herald, 2026)
This article presents the results of Post-BuildIn this case, the MathematicalOh Modeland Ton the basis of the force analysis, describing the dynamics of separation of the fiber from the seed under the action of the working bodies of the two-knife system. This model will allow you to calculate the trajectory of the flyer, determine the separation time and optimize the system parameters.